(untitled) (Carte Romanze, 2023)
In El esclavo del demonio, Mira de Amescua recovers the medieval theme of the pact with the devil and the educational ideology of humanist treatises to offer a moral teaching in line with the precepts of the Council of Trent. Lisarda’s rebellion is a transgressive act according to the principles spread in the treatises on women’s education (for example, in Vives and Luján). Don Gil’s sin reflects the fall of Luzbel and the confusion of Babel. In this context, the «ladder» acquires emblematic value as a desecrating inversion of the «mystical ladder». The spectacular recovery of the motive of the demonic pact and the battle of the angels materializes the idea of the possible salvation of the sinner who, by discarding the erroneous beliefs in predestination, collaborates with the grace of God.